Activities of the International Circassian association to support the interethnic peace in the modern period - Anzor V. Kushkhabiev (Кавказология, 2023)
It has been revealed that the propaganda of the maintenance of interethnic peace at the international, federal and regional levels is a priority in the activities of the ICA in the modern period. In this activity of the ICA, the most effective and widespread were those conducted in 2014-2023 scientific and practical conferences, round tables, etc., the purpose of which is to promote: harmonization of interethnic relations, development of international and interregional cooperation using public diplomacy methods, strengthening ties with foreign compatriots, forming a favorable public opinion about Russia abroad, interaction between government bodies, public, religious and educational organizations. The active work of the ICA in the maintenance of interethnic peace was highly appreciated at the federal level. President of the Russian Federation V.V. Putin, in his address to the participants of the XIII ICA Congress, noted special recognition of the association’s efforts to maintain peace and harmony in the North Caucasus, constructive dialogue with government agencies and civil society institutions.The peacekeeping position of the ICA on the political situation in the Donetsk and Lugansk regions of Ukraine, which escalated in March 2014, was to support Russia’s policy aimed at its peaceful settlement. After the start of the special operation of the Russian Armed Forces in Ukraine (February 2022), the position of the ICA is to support this measure, criticize the founders and participants of the “Free Circassia” movement, created in Warsaw in 2022, as well as calls for the Circassian people – unite and resist the provocations of anti-Russian forces.